2020
DOI: 10.1590/1413-81232020255.07192020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 no estado do Ceará, Brasil: comportamentos e crenças na chegada da pandemia

Abstract: This study aimed to evaluate the behavioral aspects and beliefs of the population of Ceará in the face of the COVID-19 pandemic. An online questionnaire was conducted on sociodemographic aspects and opinions related to the pandemic. Absolute and relative frequencies were calculated, the association between variables was performed with Chi-square, and the level of significance was 5%. The final sample had 2,259 participants, and an association was observed between females and perceiving themselves with a high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
58

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 32 publications
1
25
0
58
Order By: Relevance
“…Week (Lima et al, 2020) showed that some beliefs of the interviewees are similar to the government speeches denying the seriousness of the pandemic. For the group aged 80 and over, the pandemic in Brazil would be less severe than in many countries; Brazilians would have superior virus protection to people in other countries; and the warm climate of the Northeast of the country would favor the reduction of the pandemic in the region.…”
Section: Discussionmentioning
confidence: 84%
“…Week (Lima et al, 2020) showed that some beliefs of the interviewees are similar to the government speeches denying the seriousness of the pandemic. For the group aged 80 and over, the pandemic in Brazil would be less severe than in many countries; Brazilians would have superior virus protection to people in other countries; and the warm climate of the Northeast of the country would favor the reduction of the pandemic in the region.…”
Section: Discussionmentioning
confidence: 84%
“…Em um estudo (8) realizado no início do decreto do isolamento social (19 de março de 2020), os grupos compostos por homens, pessoas com baixa escolaridade e residentes no interior do estado do Ceará eram mais resistentes à adoção de isolamento social voluntário, concordando com os resultados do presente estudo.…”
Section: Perguntasunclassified
“…Para a implementação de medidas de isolamento social é necessário levar também em consideração as condições de vulnerabilidade de determinados subgrupos populacionais, como famílias de baixa renda, moradores em situação de rua, pessoas com deficiência e idosos (8,13) . Uma atenção maior deve ser dada aos idosos, uma vez que apresentaram maior taxa de comorbidades.…”
Section: Perguntasunclassified
See 1 more Smart Citation
“…A transmissão de pessoa para pessoa ocorre principalmente pelo contato direto ou por gotículas espalhadas pela tosse ou espirro de um indivíduo infectado. Sendo assim, o combateà disseminação da COVID-19 preconiza lavar as mãos frequentemente, evitar abraços, beijos e apertos de mãos e adotar medidas de afastamento social, como quarentena [Lima et al 2020].…”
Section: Covid-19unclassified